A narrative review of exercise intervention mechanisms for post-traumatic stress disorder in veterans - Fang Zhao; Chuchen Liu; Zhiyi Lin (Frontiers in Public Health)
Post-traumatic stress disorder (PTSD) severely disrupts the daily lives of veterans and active duty personnel and may influence their suicidal behaviour. This study provides insight into existing research on PTSD in veterans through a narrative review. Exercise was found to reduce PTSD symptoms in veterans at both psychological and physiological levels, which in turn inhibits their suicidal tendencies. At the psychological level, exercise improved veterans’ Subjective Well-Being and Psychological Well-Being, and at the physiological level, it improved veterans’ brain structure, neuroendocrine system, and immune system. By combing these mechanisms in detail, we hope to provide theoretical support for the implementation of exercise interventions in the treatment of veterans with PTSD. However, it is important to note that the specifics of the exercise program, such as the optimal type, dosage, and duration to alleviate PTSD symptoms, remain unclear and require further research and exploration.